The Different Perceptions of Public and Private Hospital Staff on Comprehensive Neonatal Obstetric Care - Winda Azmi Meisari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
This study discusses the staff's understanding of an existing maternal and neonatal program in Indonesia, namely the PONEK (Comprehensive Neonatal Emergency Obstetrics Services) program which is specifically held in Government Hospital or Private Hospital which is designated as PONEK hospital, research This focuses on comparing the performance of staff to the PONEK program of the hospital. The role of medical staff in running a program of health organizations is very influential in the success of a health program and service delivery. PONEK is a government program in order to minimize health problems in Indonesia, especially maternal and infant morbidity. This study aims to see differences in staff perceptions related to understanding the performance of ponek program. Method: The total number of samples in this study were 41 respondents (21 respondents Government Hospital and 19 respondents Private Hospital), statistical analysis used in this study is Mann Whitney. Result: Of the 6 factors that affect the performance, there are 2 factors that have a significant difference, that is cooperation factor with p-value 0,01 <ɑ (0,05) and support of superior with p-value 0,024 <ɑ (0,05). Conclusion: From the above results, the performance of private hospital employees compared to government hospitals has significant differences in terms of cooperation factors and support factors of supervisors.